Hemodynamic Changes in Women With Symptoms of Supine Hypotensive Syndrome. Issue 1 (24th March 2021) - Humphries, A.; Mirjalili, S.A.; Tarr, G.P.; Thompson, G.M.D.; Stone, P.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:631–636) Supine hypotensive syndrome (SHS), while lacking a clear universal definition, is sometimes defined as a drop in systolic blood pressure from 15 to 30 mm Hg or an increase in heart rate of 20 bpm when in the supine position. Inadequate collateral venous circulation has been thought to explain the etiology of SHS but this has not been well-studied. This study aimed to measure blood flow in women with symptoms of SHS, in both the supine and left lateral positions with particular attention to the azygos vein, and compare these to measurements in asymptomatic women.